Seroprevalence of Canine Ehrlichiosis and Microscopic Screening for Canine Babesiosis in Dogs in Harare, Zimbabwe, 2016-2017 - Solomon Dhliwayo; Brighton Chihambakwe; Knowledge Taonezvi; Silvester M. Chikerema; Musavengana T. Tivapasi; Davies M. Pfukenyi (Veterinary Medicine International)
A cross-sectional study was done to determine ehrlichiosis seroprevalence and babesiosis prevalence in dogs that were presented to selected veterinary clinics in Harare. Sera from randomly selected dogs were tested for antibodies to Ehrlichia spp. using an enzyme-linked immunosorbent assay while microscopy of peripheral blood smears was used to confirm babesiosis. Overall, 75.2% (88/117, 95% CI: 66.2–82.5) of sera samples tested were positive to Ehrlichia spp. antibodies while the prevalence of canine babesiosis was 47.9% (56/117, 95% CI: 38.6–57.3). Age, breed, and sex were found not to be associated with the two disease conditions p>0.05. Most of the dogs with babesiosis (82.1%, 46/56) were also positive to Ehrlichia spp. antibodies. Hypoalbuminaemia (53.8%, 63/117), anaemia (53.0%, 62/117) and thrombocytopaenia (40.2%, 47/117) were the most common laboratory findings. Thrombocytopaenia and hypoalbuminaemia was more pronounced in dogs with babesiosis only while anaemia was more marked in dogs with babesiosis and positive to Ehrlichia spp. antibodies.